2019
DOI: 10.3390/genes10040268
|View full text |Cite
|
Sign up to set email alerts
|

Neural Ganglia Transcriptome and Peptidome Associated with Sexual Maturation in Female Pacific Abalone (Haliotis discus hannai)

Abstract: Genetic information of reproduction and growth is essential for sustainable molluscan fisheries and aquaculture management. However, there is limited knowledge regarding the reproductive activity of the commercially important Pacific abalone Haliotis discus hannai. We performed de novo transcriptome sequencing of the ganglia in sexually immature and mature female Pacific abalone to better understand the sexual maturation process and the underlying molecular mechanisms. Of the ~305 million high-quality clean re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 77 publications
(117 reference statements)
0
30
0
Order By: Relevance
“…Several recent studies have identified a number of reproductive and metabolic genes in H. discus hannai (Mendoza-Porras et al 2014;Kim et al 2017). Additionally, neuropeptide precursors that influence sexual maturation in female Pacific abalone have been recently reported by Kim et al (2019). In the present study, neuropeptide transcripts were identified and characterized from the pleuropedal and cerebral ganglia of H. discus hannai to provide valuable resources for future neuroendocrine research in abalone species.…”
Section: Introductionmentioning
confidence: 79%
“…Several recent studies have identified a number of reproductive and metabolic genes in H. discus hannai (Mendoza-Porras et al 2014;Kim et al 2017). Additionally, neuropeptide precursors that influence sexual maturation in female Pacific abalone have been recently reported by Kim et al (2019). In the present study, neuropeptide transcripts were identified and characterized from the pleuropedal and cerebral ganglia of H. discus hannai to provide valuable resources for future neuroendocrine research in abalone species.…”
Section: Introductionmentioning
confidence: 79%
“…While Idgf4 does not have chitinase activity, it likely promotes cell growth and development, the function of which is unclear in the post-mitotic adult brain 59 . Idgf4 expression was positively correlated with sexual maturation in the neural ganglia of the female Pacific abalone (Haliotis discus hannai) 60 , implying that it has broad maturation-related functionality in different tissue types, including neural.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the peak expression levels of NPF in H. discus hannai and H. gigantea occurred at ZT8 (20:00 h), which was 4 h earlier than the feeding behavior peak, possibly because of the role of NPF in facilitating the feeding behavior of abalone. The amino acid sequence of the neuropeptide group of NPF in H. discus hannai has been determined (Kim et al, 2019). Thus, in future studies, the role of NPF in facilitating the feeding behavior of H. discus hannai could be validated by directly injecting Hdh-NPF.…”
Section: Discussionmentioning
confidence: 99%